1981
DOI: 10.1159/000194413
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of Postbronchoscopically Collected Sputum Samples and Its Diagnostic Value

Abstract: The usefulness of the cytology of postbronchoscopically collected sputum (PBS) samples in the diagnosis of neoplastic lung disease has been studied in 113 cases. The overall diagnostic yield of fiberoptic bronchoscopy (FB) alone was 77%, 87% in 77 central tumors and 58% in 36 peripheral ones. With the addition of PBS, the positive results increased to 91% in the 113 cases (p < 0.01), to 94% in central tumors (p > 0.05) and to 83% in peripheral lesions (p < 0.02). In 15 cases PBS offered the unique positive res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Many, relatively old, studies have shown a wide range of sensitivities of sputum cytology screening for atypical and/or malignant cells in different study populations with different risks and exposures. Positive results were ranging down to 40% in peripheral tumours and up to 90% in more central cancers [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. We found positive sputum results in 21% of our recruited patients.…”
Section: Discussionmentioning
confidence: 85%
“…Many, relatively old, studies have shown a wide range of sensitivities of sputum cytology screening for atypical and/or malignant cells in different study populations with different risks and exposures. Positive results were ranging down to 40% in peripheral tumours and up to 90% in more central cancers [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. We found positive sputum results in 21% of our recruited patients.…”
Section: Discussionmentioning
confidence: 85%